2012
DOI: 10.2355/isijinternational.52.1856
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Elements on Peritectic Reaction in Molten Steel Based on Thermodynamic Analysis

Abstract: The characteristics of the steel solidification in continuous casting, especially the peritectic reaction, have a considerable effect on the surface quality of the cast blanks. This study employed the FactSage software and thermodynamic calculation to determine the effects of various elements on the carbon content at the peritectic point (Cp) at equilibrium conditions for regular carbon and low alloy steels. . Furthermore, the accuracy for the carbon content at the peritectic reaction was indirectly validated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 4 publications
1
15
0
Order By: Relevance
“…Also, the present set of calculated values for Tγ correlates excellently with those calculated by Xu et al 5) using Factsage and both of these values are slightly higher than the measured values. This is because the calculated values are for equilibrium conditions while the measured data are for actual industrial (non-equilibrium) conditions.…”
Section: Validation With Literature Datasupporting
confidence: 88%
See 4 more Smart Citations
“…Also, the present set of calculated values for Tγ correlates excellently with those calculated by Xu et al 5) using Factsage and both of these values are slightly higher than the measured values. This is because the calculated values are for equilibrium conditions while the measured data are for actual industrial (non-equilibrium) conditions.…”
Section: Validation With Literature Datasupporting
confidence: 88%
“…5,6) The present model represents a greater value of R 2 and a smaller value of RMSD (Root Mean Square Deviation). It can thus be concluded that in the composition ranges considered here, the present correlation fits the calculated data much better than any of the pre-existing models.…”
Section: Validation With Literature Datamentioning
confidence: 78%
See 3 more Smart Citations